Investigation of the Effect of 60% of the Addition of Latex on Asphalt Pen 60-70 - Barus, Diana Alemin (Journal of Technomaterial Physics, 2020)
This study discussed the increase of latex 60% addition to obtain the standard of asphalt 60-70. The comparison used were without the increase of latex addition (L0), 1000 g penetration of asphalt 60-70 with 100 g latex with 60 % degree or 10 phr ( L1), 1000 g penetration of asphalt 60-70 with 200 g latex 60 % degree or 20 phr ( L2), 1000 g penetration of asphalt 60-70 with 300 g latex 60 % degree or 30 phr ( L3), 1000 g penetration of asphalt 60-70 with 400 g latex 60 % degree or 40 phr ( L4). All of the samples homogenized by heating at 150ÂºC temperature and 250 rpm within 30 minutes then soaked in the tub for 30 minutes at 25ÂºC.